2011
DOI: 10.1136/jfprhc-2011-100106
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing in colposcopy and termination of pregnancy services: a missed opportunity?

Abstract: IntroductionThe 2008 National HIV testing guidelines produced jointly by the British Association of Sexual Health and HIV, British HIV Association and British Infection Society recommend HIV testing for patients attending termination of pregnancy (TOP) services and patients diagnosed with cervical intraepithelial neoplasia (CIN) Grade 2 or above. The aim is to reduce the time between acquisition and diagnosis of HIV by encouraging testing in settings where patients present with indicator diseases. Benefits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…The high uptake, especially among women who had never previously had an HIV test, suggests that this approach may target an at-risk population who might not attend for HIV testing in more traditional settings. When combined with the high positivity rate we concur with Bates and Briggs et al's conclusions of promoting more widespread HIV testing in TOP and colposcopy services 1 2…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The high uptake, especially among women who had never previously had an HIV test, suggests that this approach may target an at-risk population who might not attend for HIV testing in more traditional settings. When combined with the high positivity rate we concur with Bates and Briggs et al's conclusions of promoting more widespread HIV testing in TOP and colposcopy services 1 2…”
supporting
confidence: 88%
“…We read with interest the article by Briggs et al1and associated commentary by Bates2 suggesting a widening of HIV testing venues, to include termination of pregnancy services (TOP) and colposcopy services.…”
mentioning
confidence: 99%
“…36 Regarding missed opportunities, a British case notes review of 60 women diagnosed with HIV between 2006 and 2009 reported that HIV testing at the time of TOP may have resulted in earlier HIV diagnosis in 5% of cases. 37 In Lausanne, Switzerland, among 75 women newly diagnosed with HIV between 2011 and 2015, 34 had presented at least one missed opportunity for earlier HIV diagnosis, of whom 5 (14.7%) had not been tested when seeking TOP (Lhopitallier L, personal communication, 2021). 38…”
Section: Top History Among Wwh and Missed Opportunities For Earlier Hiv Diagnosismentioning
confidence: 99%
“…It has been previously recognised that health care providers in the UK have opportunities to initiate HIV testing in at risk individuals and address the burden of undiagnosed HIV infection (22–24). The majority of people living with HIV seek medical care for a related condition several times in the 6 months prior to their HIV diagnosis, presenting to general medicine and outpatient settings including primary care (21,25).…”
Section: The Imperative To Increase Hiv Testingmentioning
confidence: 99%